Vernacularizing Sunni Orthodoxy in the Malay-Indonesian World: Shaykh Abdurrahman Shidiq al-Banjari’s Theological and Pedagogical Works - Jovita Dara Yuda; Dian Mursyidah; Mina Zahara; Ahmad Barakati Jalhani (Graduate School of UIN Syarif Hidayatullah Jakarta, 2026)
This study examines the intellectual legacy of Shaykh Abdurrahman Shidiq bin Shaykh Muhammad Afif al-Banjari (c. 1857–1939), a distinguished Nusantaran scholar who served as Mufti of the Indragiri Kingdom during a period of profound colonial, social, and religious transformation. His scholarly contributions represent a synthesis of Islamic theology, Sufism, and education within the Ahlussunnah wal Jama‘ah tradition, reflecting the dynamics of Islamic knowledge production in the Malay-Indonesian world. The study aims to reconstruct his intellectual biography, analyze his principal writings, and evaluate the relative significance of five extant works that remain accessible to contemporary scholarship. Employing the historical method, the research follows four stages: heuristic, source verification, interpretation, and historiography. Primary data were obtained from printed works authored by Shaykh Abdurrahman Shidiq, complemented by secondary historical literature and preliminary interviews with local religious figures and scholars familiar with his intellectual heritage. The findings indicate that existing literature attributes at least sixteen works to Shaykh Abdurrahman Shidiq, covering the fields of theology, jurisprudence, ethics, Sufism, and Islamic education. Among the surviving texts, ‘Aqā’id al-Īmān appears, based on available textual evidence and field observations, to be the most widely studied in pesantren traditions, particularly in Indragiri and South Kalimantan. The study concludes that Shaykh Abdurrahman Shidiq made a substantial contribution to the development of Islam Nusantara through the transmission of Sunni scholarship and religious education. At the same time, this historical-textual reconstruction underscores the importance of systematic manuscript cataloguing, archival verification, and critical philological research to preserve and deepen understanding of Indonesia’s Islamic intellectual heritage.